1977
DOI: 10.1115/1.3446288
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Segment Parallel Compressor Model for Circumferential Flow Distortion

Abstract: A nonlinear compressible flow model has been developed for the prediction of compressor performance and stability with a circumferential flow distortion. This model uses multiple parallel compressor segments and accounts for deviations from undistorted compressor performance. It is applicable to large-amplitude inlet distortions of total pressure and/or temperature, as well as circumferential variations in exit static pressure. The basic model requires the undistorted performance characteristics for each blade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
2

Year Published

1980
1980
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 0 publications
0
55
0
2
Order By: Relevance
“…Historically, in order to provide a simple yet effective model to predict stability margin of a compressor with inlet distortion, many efforts including various small perturbation theories [1] , parallel compressor models [2] , actuator disk theories [3] , and Moore-Greitzer based inertia parameter models [4][5] have been made. Longley et al [6] studied several multistage low-speed compressors with various RID and concluded that the excitation-and-response theory based on the 2D H-G model matched nicely with the test results of those compressors that exhibited only one peak in the response curve of stall margin shift versus distortion rotation speed, but failed to make a good agreement with those machines which had two peaks in the same kind of response curve.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, in order to provide a simple yet effective model to predict stability margin of a compressor with inlet distortion, many efforts including various small perturbation theories [1] , parallel compressor models [2] , actuator disk theories [3] , and Moore-Greitzer based inertia parameter models [4][5] have been made. Longley et al [6] studied several multistage low-speed compressors with various RID and concluded that the excitation-and-response theory based on the 2D H-G model matched nicely with the test results of those compressors that exhibited only one peak in the response curve of stall margin shift versus distortion rotation speed, but failed to make a good agreement with those machines which had two peaks in the same kind of response curve.…”
Section: Introductionmentioning
confidence: 99%
“…One of the methods used was a linearized approach (Greitzer 1980;Plourde and Stenning 1967) that provides a quantitative information about the performance of the compressor in a circumferentially non-uniform flow. Several models (Greitzer 1980;Mikolajczak and Pfeffer 1974), such as the parallel compressor model and its extensions (Mazzawy 1977), were used to assess the compressor stability with inlet distortion.…”
Section: Introductionmentioning
confidence: 99%
“…Physical speed of the gas generator (N) and power turbine (Np) were the control parameters in the steady-state control strategy. (1) where W is mass flow; subscript GT,Cooling is Gas turbine cooling air from compressor.…”
Section: Figure 2 Division Of Circumferential Inlet Flow Distortionmentioning
confidence: 99%
“…Whatever the source, the performance and stability of the aeroengine generally reduced. Even the blade rupture fault occurred when the compressor surged caused by inlet flow distortion [1].…”
Section: Introductionmentioning
confidence: 99%